The Danish SSP model – prevention through support and co-operation. Issue 4 (7th December 2015) - Pedersen, Jørgen; Stothard, Blaine
Abstract : Purpose: – The purpose of this paper is to provide an outline of the origins, rationale and ways of working of the Danish schools, social services, police (SSP) system. Design/methodology/approach: – Narrative account of origins and contexts and discussion of implications for other nations and contribution to knowledge of prevention work. Findings: – The SSP system represents an involvement by Danish state institutions in the welfare and development of young people. Practice indicates its broad acceptance by parents, young people and professionals. Recent extension of SSP work is demonstrating some of the limitations of the approach in working with alienated young people. Research limitations/implications: – The present SSP system relies on local evaluation and assessment. Wider national and longitudinal evaluation needs further consideration. Practical implications: – The need for a career structure and continuing and nationally consistent professional development opportunities was identified in a previous evaluation. Social implications: – SSP enjoys broad acceptance amongst parents, young people and professionals in that it provides a universal input into young people's well-being and social integration. It is proving less successful in work in some urban areas with high levels of alienation amongst older young people. There is also a need for re-statement of confidentiality aspects. Originality/value: – The paper provides an insight into and overview of a cross-disciplinary approach to young people's development and well-being where the state plays a key and accepted role. The rationale is equally relevant to the UK and other countries.